2015
DOI: 10.4103/1947-2714.168675
|View full text |Cite
|
Sign up to set email alerts
|

Deficiencies under plenty of sun: Vitamin D status among adults in the kingdom of Saudi Arabia, 2013

Abstract: Background:Vitamin D deficiency has been correlated with several diseases and injuries including diabetes, osteoporosis, fractures, and falls. In the Kingdom of Saudi Arabia (KSA), current data on vitamin D status are lacking.Aims:To inform Saudi public health authorities on the current status of blood levels vitamin D deficiency, we analyzed data from the Saudi Health Interview Survey.Materials and Methods:The Saudi Health Interview Survey (SHIS) is a cross-sectional national multistage survey of individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 24 publications
5
27
0
Order By: Relevance
“…Moreover, the worryingly high prevalence of hypovitaminosis D observed here is in line with the findings of some previous studies in the Middle Eastern context, and specifically in Saudi Arabia, which also identified a high prevalence 17. For example, a recent cross-sectional research in Saudi Arabia using a sample of healthy female subjects aged 15 to 24 years revealed that 56.6% had vitamin D insufficiency 29. Along similar lines, a cross-sectional research in Qatar which used a sample of healthy female university students concluded that almost all the participants had vitamin D insufficiency (more precisely, the sample had a strikingly high prevalence of 97.2%) 30.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, the worryingly high prevalence of hypovitaminosis D observed here is in line with the findings of some previous studies in the Middle Eastern context, and specifically in Saudi Arabia, which also identified a high prevalence 17. For example, a recent cross-sectional research in Saudi Arabia using a sample of healthy female subjects aged 15 to 24 years revealed that 56.6% had vitamin D insufficiency 29. Along similar lines, a cross-sectional research in Qatar which used a sample of healthy female university students concluded that almost all the participants had vitamin D insufficiency (more precisely, the sample had a strikingly high prevalence of 97.2%) 30.…”
Section: Discussionsupporting
confidence: 92%
“…Other sources of dietary vitamin D include fortified foods (usually milk and other dairy products, margarine and spreads, and some breakfast cereals) and dietary supplements 46. However, prior research suggests that the fortification level present in dairy products is insufficient to prevent vitamin D deficiency,47 and that Saudi women rarely consume vitamin D supplements 29. Therefore, the design of effective policies able to encourage intakes which will support a healthy vitamin D status represents a strategic challenge for government.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Alsuwaida et al stated that 50% of study participants had adequate vitamin D levels ≥ 30 ng/mL [38]. A national survey conducted in Saudi Arabia in 2013 among Saudis from both genders aged 15 years and above reported that vitamin D deficiency (<28 ng/mL) was prevalent among 40.6% of males and 62.6% of females [39]. …”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional national survey, Tuffaha et al examined 10,735 Saudi patients aged ≥15 years and found that 40.6% of men had serum 25(OH)D < 70 nmol/L [39]. A retrospective study by Hussain et al reported similar data from 10,709 Saudi patients, with 40.2% and 53.5% of men ( n = 3363) reported as having vitamin D deficiency and insufficiency/inadequacy at 25(OH)D < 25 and 25–75 nmol/L, respectively [23].…”
Section: Prevalence Of Micronutrient Deficiencies In the Middle Eastmentioning
confidence: 99%